FCNC transitions of $$Λ _b$$ Λb to neutron in Bethe–Salpeter equation approach - Liang-Liang Liu; Chao Wang; Xian-Wei Kang; Xin-Heng Guo (European Physical Journal C: Particles and Fields, 2020)
Abstract In a covariant quark–diquark model, we investigate the rare decay of $$Λ _b → n l^+ l^-$$ Λb→nl+l- and $$Λ _b → n γ $$ Λb→nγ in the Bethe–Salpeter equation approach. In this model the baryons are treated as bound states of a constituent quark and a diquark interacting via a gluon exchange and the linear confinement. We find that the ratio of form factors R is varies from $$-0.90$$ -0.90 to $$-0.25$$ -0.25 and the branching ratios $$Br(Λ _b → n l^+ l^-)× 10^{8}$$ Br(Λb→nl+l-)×108 are $$6.79(l=e),~4.08 ~ (l=μ ),~2.9 ~(l=τ ) $$ 6.79(l=e),4.08(l=μ),2.9(l=τ) and the branching ratio $$Br(Λ _b → n γ )× 10^{7} )=3.69$$ Br(Λb→nγ)×107)=3.69 in central values of parameters.